Effects of Home Value, Home Age, and Lot Size on Lawn Watering Practices of Residential Homeowners - D. Bremer; S. Keeley; A. Jager (Kansas Agricultural Experiment Station Research Reports, 2015)
Lawn care and lawn watering practices of residential homeowners were significantly affected by home value and home age, but lot size was less a factor.
Keywords: turfgrass; lawn care; lawn watering; water conservation; residential lawn